Design, Fabrication, and Mechanism of Nitrogen‐Doped Graphene‐Based Photocatalyst. Issue 9 (18th January 2021) - Bie, Chuanbiao; Yu, Huogen; Cheng, Bei; Ho, Wingkei; Fan, Jiajie; Yu, Jiaguo
Abstract: Solving energy and environmental problems through solar‐driven photocatalysis is an attractive and challenging topic. Hence, various types of photocatalysts have been developed successively to address the demands of photocatalysis. Graphene‐based materials have elicited considerable attention since the discovery of graphene. As a derivative of graphene, nitrogen‐doped graphene (NG) particularly stands out. Nitrogen atoms can break the undifferentiated structure of graphene and open the bandgap while endowing graphene with an uneven electron density distribution. Therefore, NG retains nearly all the advantages of original graphene and is equipped with several novel properties, ensuring infinite possibilities for NG‐based photocatalysis. This review introduces the atomic and band structures of NG, summarizes in situ and ex situ synthesis methods, highlights the mechanism and advantages of NG in photocatalysis, and outlines its applications in different photocatalysis directions (primarily hydrogen production, CO2 reduction, pollutant degradation, and as photoactive ingredient). Lastly, the central challenges and possible improvements of NG‐based photocatalysis in the future are presented. This study is expected to learn from the past and achieve progress toward the future for NG‐based photocatalysis. Abstract : Nitrogen‐doped graphene plays a significant role in photocatalysis. Rational design, preparation, and understanding the mechanism of N‐doped graphene‐based photocatalysts provides a new opportunity to further enhance the photocatalytic performance. The research progress, atomic and band structures, photocatalytic mechanism, synthesis strategy, unique advantages, and wide application of N‐doped graphene in photocatalysis are highlighted.